Scaling deep at the margins: coproduction of nature-based solutions as decolonial research praxis in Cape Town - Patience Mguni; Lise Byskov Herslund; Amber Louise Abrams; Kirsty Carden; Craig Tanyanyiwa; Julia McLachlan; Rachelle Schneuwly; Neil Armitage (npj Urban Sustainability)
Abstract In this paper, we use a decolonial lens to reflect on a place-based transdisciplinary Nature-based Solutions (NbS) research project that focussed on the multifunctional retrofitting of a stormwater detention pond through coproduction in Mitchells’ Plain, Cape Town. We find that stormwater ponds represent promising yet contested leverage points for coproducing NbS towards water resilience in Cape Town. We also find that ‘scaling deep at the margin’ is an important initial condition for experimenting with NbS in contexts of deep difference. Here resistance and desire are central dynamics that may help rework the unjust power asymmetries in the post-apartheid city. Researchers need not foreclose the possibilities of failure in transdisciplinary NbS experiments when resistance is encountered, instead they should explore the generative insights that may result from failure. We conclude that sustainability transitions in the Global South may be more productively understood as contested, seldom-complete endeavours in which justice remains the goal.